ANALISIS PENGARUH MOTIVASI KERJA, LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) TENAGA PENDIDIK - Dwi Susilo; Ari Muhardono (Fakultas Ekonomi Universitas Pekalongan, 2021)
Pekalongan University is one of the universities that was also affected by the Covid 19 virus in Indonesia, where new student admissions have decreased for the last 3 years. The effect of declining student acceptance which is the main source of funding can result in disruption of higher education operations, therefore a solution is needed to overcome this problem, one of which is by increasing the awareness of all Pekalongan University academics to participate in maintaining efficiency in spending. One of the ways to reduce expenditure efficiency is by making savings in electricity consumption, which is a fairly high expenditure post at Pekalongan UniversityThis study aims to examine and analyze whether there is a significant effect of Work Motivation, Work Environment, and Compensation on Organizational Citizenship Behavior (OCB) of Unikal educators.This study uses multiple regression analysis techniques. Data were obtained from questionnaires distributed online to permanent lecturers at Pekalongan University, totaling 83 samples.The results of this study indicate that there is a significant positive effect of Work Motivation, Work Environment, and Compensation on Organizational Citizenship Behavior of Unikal educators. The most dominant variable affecting Organization Citizen Behavior is the work motivation variable